2020
DOI: 10.1002/rmv.2185
|View full text |Cite
|
Sign up to set email alerts
|

Alternative clinical specimens for the detection of SARS‐CoV‐2: A rapid review

Abstract: The collection of nasopharyngeal swabs to test for the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an invasive technique with implications for patients and clinicians. Alternative clinical specimens from the upper respiratory tract may offer benefits in terms of collection, comfort and infection risk. The objective of this review was to synthesise the evidence for detection of SARS-CoV-2 ribonucleic acid (RNA) using reverse transcription polymerase chain reaction (RT-PCR) tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
(288 reference statements)
3
26
0
Order By: Relevance
“…For an accurate comparison of saliva and NPS specimens, the same extraction method and RT-qPCR systems, with identical experiment control and validation criteria, were used. Overall, the present study confirmed the relevance of the saliva sampling for SARS-CoV-2 detection in the 303 individuals under investigations, with a concordance to NPSs exceeding 90%, that was among the more efficient [19]. Nevertheless, among the 58 participants classified SARS-CoV-2 positive either by NPS and/or saliva tests, discordant paired detection represented half of them (n=29).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For an accurate comparison of saliva and NPS specimens, the same extraction method and RT-qPCR systems, with identical experiment control and validation criteria, were used. Overall, the present study confirmed the relevance of the saliva sampling for SARS-CoV-2 detection in the 303 individuals under investigations, with a concordance to NPSs exceeding 90%, that was among the more efficient [19]. Nevertheless, among the 58 participants classified SARS-CoV-2 positive either by NPS and/or saliva tests, discordant paired detection represented half of them (n=29).…”
Section: Discussionsupporting
confidence: 82%
“…Although reports about the screening properties accuracy of saliva for COVID-19 are more and more numerous [1517], this biological fluid remains dispraised due to its variable diagnostic performance compared to nasopharyngeal swab (NPS) [18]. The discrepancy observed could be attributed to several factors, such as the heterogeneity of saliva specimens (eg, spitting saliva, posterior oropharyngeal, deep throat saliva, drooling collection), the saliva collection methods (eg, swabs, widemouth tube, funnel, soother), or the target population (eg, hospitalized inpatients, clinically suspected cases, symptomatic, asymptomatic, healthcare workers) [19]. To control the ongoing COVID-19 pandemic and to prevent the emergence of new foci of infection, the mass detection of symptomatic and asymptomatic individuals has become essential [20].…”
Section: Introductionmentioning
confidence: 99%
“…From the analytical viewpoint, it is widely agreed that the sensitivity of rRT-PCR of NPS ranges from 70 to 90% (5,8), reaching values around 50% after the first two weeks of disease (9,10). Therefore, COVID-19 disease cannot be ruled out when a NPS result is negative, but the patient has clinical symptoms, and biochemical data and radiological findings that evidence a clinical scenario typical of the disease (11).…”
Section: /27mentioning
confidence: 99%
“…Although the molecular detection of SARS-CoV-2 RNA in naso-pharyngeal swabs (NPS) is considered the “gold standard” technique for identifying symptomatic or asymptomatic individuals (7), it has limitations in both the analytical and the healthcare settings. From the analytical viewpoint, it is widely agreed that the sensitivity of rRT-PCR of NPS ranges from 70 to 90% (5,8), reaching values around 50% after the first two weeks of disease (9,10). Therefore, COVID-19 disease cannot be ruled out when a NPS result is negative, but the patient has clinical symptoms, and biochemical data and radiological findings that evidence a clinical scenario typical of the disease (11).…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to point out that salivary gland epithelial cells can be infected by SARS-CoV a short time after infection in rhesus macaques, suggesting that salivary gland cells could be a pivotal source of this virus in saliva [12]. However, there have been conflicting studies on the presence of SARS-CoV2 virus in the saliva sample of infected patients [1][2][3][4]8,13]. Thus, this research project aims to study the presence of SARS-CoV-2 in the saliva of suspected COVID-19 patients in comparison to its presence in NP swabs.…”
Section: Variety Of Sars-cov-2 Detection Methods Are Available; Nasomentioning
confidence: 99%